Ecotoxicology effects of pollutants on the natural environment - Walker, Colin (CRC Press, Taylor and Francis Group, 2014)
Chemical Warfare in NaturePesticides and other industrial chemicals are at the root of many pollution problems. In view of the toxic effects of industrial chemicals found in the water, soil, and air, Ecotoxicology: Effects of Pollutants on the Natural Environment considers the impact of chemicals on the environ-ment from a wider perspective: the evolution of plant toxins-and defense mechanisms against them in animals as a consequence of plant-animal warfare. Comparisons are made between this and the development of resistance by insects towards man-mad.